Nonoscillation of the solutions of impulsive differential equations of third order. (2001) - Dimitrova, Margarita Boneva
Abstract : Necessary and sufficient conditions are found for existence of at least one bounded nonoscillatory solution of a class of impulsive differential equations of third order and fixed moments of impulse effect. Some asymptotic properties of the nonoscillating solutions are investigated.